Local Josephson vortex generation and manipulation with a Magnetic Force Microscope - Viacheslav V. Dremov (Nature Portfolio, 2019)
Josephson vortices (JVs) play an important role in superconducting quantum devices, but they remain difficult to be observed and manipulated. Here, Dremov et al. report magnetic fingerprint of JVs in magnetic force microscopy experiments, which paves a way to generate and control JVs.